Extreme return spillovers and connectedness between crude oil and precious metals futures markets: Implications for portfolio management. (December 2022) - Alomari, Mohammad; Mensi, Walid; Vo, Xuan Vinh; Kang, Sang Hoon
Abstract: This paper examines quantile return spillovers and the connectedness between crude oil futures and key precious metals (PMs) using the approach developed by Ando et al. (2022). Our findings show that using the cross-quantilogram directional spillover method results in significant spillovers from oil to PMs under an extreme downside oil market scenario. Oil impacts both palladium and platinum under an extreme upside oil market status. Under normal oil market conditions, we show insignificant spillovers from oil to PMs. We find an insignificant dependence of PMs on oil during bearish markets, indicating that PMs serve as a safe haven asset. However, we find that oil and palladium are net receivers of spillovers across quantiles, except for palladium at intermediate quantiles, and other PMs are net contributors of spillovers across all quantiles. The spillovers are higher at extreme quantiles and increase during extreme events. Furthermore, we find no connection between platinum and gold under normal market conditions and a weak connection between platinum and both silver and palladium during bearish market scenarios. Precious metals are good diversifying assets for oil portfolios. The hedging strategy using PMs is less expensive during the COVID-19 pandemic than before it, with the exception of platinum. Finally, PMs offer higher hedging effectiveness before the pandemic crisis, whereas palladium provides the highest hedging effectiveness before and during the pandemic crisis. Highlights: Quantile return connectedness between crude oil futures and precious metals. Oil and palladium are net receivers of spillovers across quantiles. The spillovers are higher at extreme quantiles and increase during extreme events. Precious metals are good diversifying assets for oil portfolios. Precious metals offer a higher hedging effectiveness before the pandemic crisis.